Upadłość konsumencka - szansa czy zagrożenie? - Gurgul, Stanisław (Consumer Insolvency - Chance Or Danger?, 2008)
Following other countries, it is planned to put into effect consumer insolvency, aimed for natural persons not running business. In the author's opinion, this is a very damaging solution, which threatens the equality of all citizens before the law, threatens the development of a vibrant, honest enterprising. Remitting debts of unreliable, morally sick persons means simply supporting pathology and may cause over the years the destruction of society, and as consequence the total collapse of today's civilizations called democracies. We can only hope that Polish politicians do not stoop to demagogy of the World International and will protect our country against these effects
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 216-222